Evagrius of Pontus’ Christology - Kaminis, Ioannis (Forum Theologicum Sardicense, 2025)
Ioannis Kaminis, Evagrius of Pontus' Christology. This paper reconstructs the Christology of Evagrius Ponticus according to his fundamental works, his Epistles, Kephalaia Gnostica and Commentary on the Psalms. In order to elucidate current problematics surrounding his Christology, this paper explores the Christology of Evagrius in the context of his time and taking also into consideration the most recent studies on his theological system. In his so called Epistle on Faith Evagrius follows the teaching of the Cappadocian Fathers and based on this he expands his view on Jesus Christ. However many of his remarks on Jesus Christ are ambiguous and can also be interpreted in a way which contradicts the Orthodox teaching. Apart from this, one cannot comprehend the Evagrian Christology without connecting it with his whole theological system of spiritual ascension comprised by practice (πρακτικη) contemplation of nature (φυσικη) and theology (θεολογια). The origenist influence is more evident in his magnum opus Kephalaia Gnostica and this work is his most controversial, not only because of its origenism but also because of other cosmological and theological teachings. Nevertheless it’s obvious that Eva-grius knew about the dogmatical problems and that is why it seems that he struggles with his own ideas and teaching. Apparently what he had in mind was to provide a theological holistic system which could help every Christian believer to find a secure way to approach God.